Algal blooms seasonality along the coast of Iceland and volcanic influences from the Eyjafjallajökull eruption in 2010 - Stokkom, Anouk van, 1989- (2013)
Photosynthetic algae are at the base of the food chain and are therefore of major importance for aquatic life. The Icelandic economy is highly focused on fish industries and is therefore reliant on algae production and blooming. This research aims to map and assess the temporal and spatial pattern of algal blooms in the waters around Iceland. Furthermore, to model and analyse short term influences that catastrophic events may potentially have on the spatio-temporal distribution of algal blooms by investigating the impacts of the ash fall from the 2010 Eyjafjallajökull eruption. This is obtained firstly by using a monitoring approach to obtain an overview of the general seasonality of the algal growth around Iceland between 2007 and 2012 and thus determine both the timing and extent of the algal growth season, as well as detect the trend over time. Secondly, by using the Delft3D modelling software to analyse the potential influences of the eruption of the Eyjafjallajökull in April 2010 on the algal blooms in Selvogsbanki to examine if there is any shift in timing and extent of the algal blooming. The spatiotemporal pattern of algal blooms in Icelandic waters shows low occurrences in winter and peaking at the end of spring and beginning of summer. In 2010 chlorophyll values peaked later and higher than usual. The results indicated that algae in Selvogsbanki responded negatively to the eruption. Further research is however necessary in order to increase the accuracy; especially in regard to the spatial resolution in satellite imagery and model complexity.